2018
DOI: 10.5751/ace-01206-130116
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of Black-backed Woodpeckers following delayed salvage logging in the Sierra Nevada

Abstract: ABSTRACT. The Black-backed Woodpecker (Picoides arcticus) is a snag-associated species that colonizes and utilizes patches of burned forests typically within 10 years of fire. Previous research has indicated that salvage logging, the removal of dead and dying trees from burned forests, has a negative effect on nesting densities of Black-backed Woodpeckers. One strategy proposed to ameliorate the impacts of dead tree removal on Black-backed Woodpeckers is to retain patches, or islands, of dense snags within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Response variables are defined in Table 4 and predictor variables are defined in Table 5 more common in particular quadrats where bark beetles were absent, suggesting that the local retention of woodborers might be enhanced by prioritizing retention of trees less heavily infested by bark beetles. Our observations that woodborer larvae were more abundant in smaller pine snags with more southerly exposure, that Xylotrechus Chevrolat 1860 adults were more common where the dominant host tree taxon was true fir, and that Monochamus species were more common where burn severity was low to moderate, can further inform design of snag retention patches that might effectively promote successional processes and provide prey for wildlife species like the black-backed woodpecker (Siegel et al 2018;Tarbill et al 2018;Stillman et al 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Response variables are defined in Table 4 and predictor variables are defined in Table 5 more common in particular quadrats where bark beetles were absent, suggesting that the local retention of woodborers might be enhanced by prioritizing retention of trees less heavily infested by bark beetles. Our observations that woodborer larvae were more abundant in smaller pine snags with more southerly exposure, that Xylotrechus Chevrolat 1860 adults were more common where the dominant host tree taxon was true fir, and that Monochamus species were more common where burn severity was low to moderate, can further inform design of snag retention patches that might effectively promote successional processes and provide prey for wildlife species like the black-backed woodpecker (Siegel et al 2018;Tarbill et al 2018;Stillman et al 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Different sized patches may vary in habitat characteristics such as microclimate and amount of edge shared with green forest (Andrén 1994;Stephens et al 2013). It is an important goal to balance management objectives on a landscape to increase resilience by reducing future likelihood of high-severity fire while also leaving areas with high densities of snags, logs, and shrubs that can provide important habitat that has been lacking in firesuppressed areas (Peterson et al 2015;White et al 2016;Tarbill et al 2018). Conserving these habitat features at the appropriate scale may help to balance management objectives within large stand-replacing patches.…”
Section: Discussionmentioning
confidence: 99%
“…Post-fire management can pose as an opportunity to design and monitor treatments in such a way that the ecological impacts can be assessed and integrated into future management planning. For example, Tarbill et al (2018) examined how patterns and timing of salvage logging affected wildlife when remnant "islands" of snag habitat were preserved. Several studies have opportunistically analyzed how fuels treatments influenced subsequent fire spread and severity (e.g., Lydersen et al 2017;Johnson and Kennedy 2019;Kennedy et al 2019), but specific information on how the amount of large, dead wood on a landscape contributes to fire behavior is not well understood, and the dynamics of these fuels following treatments and wildfire are often not quantified or tracked over time due to limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that nesting Black‐backed Woodpeckers generally avoid areas with extensive post‐fire logging, particularly when private holdings are clear‐cut and replanted with conifers (Tarbill et al. 2018).…”
Section: Methodsmentioning
confidence: 99%